Assembly force and taper angle difference influence the relative motion at the stem–neck interface of bi-modular hip prostheses. (July 2016) - Haschke, Henning; Jauch-Matt, Sabrina Y; Sellenschloh, Kay; Huber, Gerd; Morlock, Michael M
Bi-modular hip arthroplasty prostheses allow adaptation to the individual patient anatomy and the combination of different materials but introduce an additional interface, which was related lately to current clinical issues. Relative motion at the additional taper interface might increase the overall risk of fretting, corrosion, metallic debris and early failure. The aim of this study was to investigate whether the assembly force influences the relative motion and seating behaviour at the stem–neck interface of a bi-modular hip prosthesis (Metha ® ; Aesculap AG, Tuttlingen, Germany) and whether this relation is influenced by the taper angle difference between male and female taper angles. Neck adapters made of titanium (Ti6Al4V) and CoCr (CoCr29Mo) were assembled with a titanium stem using varying assembly forces and mechanically loaded. A contactless eddy current measurement system was used to record the relative motion between prosthesis stem and neck adapter. Higher relative motion was observed for Ti neck adapters compared to the CoCr ones (p < 0.001). Higher assembly forces caused increased seating distances (p < 0.001) and led to significantly reduced relative motion (p = 0.019). Independent of neck material type, prostheses with larger taper angle difference between male and female taper angles exhibited decreased relative motion (p < 0.001). Surgeons should carefully use assembly forces above 4 kN to decrease the amount of relative motion within the taper interface. Maximum assembly forces, however, should be limited to prevent periprosthetic fractures. Manufacturers should optimize taper angle differences to increase the resistance against relative motion.